Tradisi Tradisi Lamaran Setara saat Alèngkaè sè Tua'an Perspektif ‘urf dan Sosiokultural Lev Vygotsky di Desa Beringin - Subaidah; Ulya, Zakiyatul (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
Beringin Village, Tambelangan District, Sampang Regency, Madura, has a unique proposal tradition called alèngkaè sè tua'an. This tradition requires the younger husband-to-be to propose to the older wife-to-be who is not yet married. From the perspective of 'urf, this practice becomes sahih ‘urf if it is done voluntarily, without burdening the prospective groom, and does not become an absolute requirement for marriage. However, it becomes a fasid ‘urf if it is considered obligatory to prevent the older sister from being labeled as an old maid, burdening the groom, or causing social sanctions such as ridicule. From Lev Vygotsky's sociocultural perspective, alèngkaè sè tua'an is more than a ritual, but a social learning process that shapes identity, strengthens family ties and reflects cultural values. This tradition highlights how social and cultural contexts influence the marriage process and its implications for community norms and family harmony.